A case of primary biliary cirrhosis and rheumatoid arthritis in a woman with a partial Di-George syndrome. Issue 2 (3rd July 2017) - Xenophontos, Eleni; Psarelis, Savvas; Papanicolaou, Eleni
Abstract: Di-George syndrome (DGS) is amongst the commonest genetic disorders caused by microdeletions in the long arm of chromosome 22, resulting in a phenotypically similar syndrome. It ultimately affects many organs and systems leading mainly to cardiac malformations, hypocalcaemia and thymic impairment. Dysfunction of the thymus was associated with immune dysfunction. The association between DGS and autoimmune diseases like primary biliary cirrhosis (PBC) and rheumatoid arthritis (RA) is under investigation. PBC is an autoimmune disease affecting the intrahepatic ducts leading to progressive cholestasis and end-stage liver disease. RA is an autoimmune chronic inflammatory disease of multiple joints. PBC and RA rarely co-exist (frequency 1.8–5.6%). Genetic, epigenetic and environmental factors play a role. In this case report, we describe the unique case of a 22-year female with a partial DGS who was initially diagnosed with PBC and a year after with RA. It is early to answer the possible reasons of the co-occurrence of the three diseases in the same patient; nevertheless, we suggest infections as a trigger.